Phosphorus plays an important role in enhancing biodiesel productivity of Chlorella vulgaris under nitrogen deficiency - Chu, Fei-Fei; Chu, Pei-Na; Cai, Pei-Jie; Li, Wen-Wei; Lam, Paul K.S.; Zeng, Raymond J. (Bioresource technology, 2013)
[Display omitted] ► P is important to enhance algal lipid productivity under nitrogen deficiency (N−). ► Lipid productivity under N− with sufficient P supply is highest as 58.39mg/L/day. ► P uptake rate under N− is 3.8 times faster than that of sufficient N&P supply. ► 31P NMR shows that uptake P is accumulated as polyphosphate in algal cells. To investigate the role of phosphorus in lipid production under nitrogen starvation conditions, five types of media possessing different nitrogen and phosphorus concentrations or their combination were prepared to culture Chlorella vulgaris. It was found that biomass production under nitrogen deficient condition with sufficient phosphorus supply was similar to that of the control (with sufficient nutrition), resulting in a maximum lipid productivity of 58.39mg/L/day. Meanwhile, 31P NMR showed that phosphorus in the medium was transformed and accumulated as polyphosphate in cells. The uptake rate of phosphorus in cells was 3.8 times higher than the uptake rate of the control. This study demonstrates that phosphorus plays an important role in lipid production of C. vulgaris under nitrogen deficient conditions and implies a potential to combine phosphorus removal from wastewater with biodiesel production via microalgae.